Exchange rates and different degrees of capital market integration: A monetary approach to the Mark/Dollar rate - Peter König (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1986)
In the political discussion, exchange rates are often said to be overvalued or undervalued. This is due to the fact that exchange rates have to fulfill a (more than) dual role: they have to balance international goods markets and international capital markets. In general, economic models try to handle this problem by introducing short-term overshooting effects of the exchange rate induced by monetary disturbances. Yet, especially in estimating these models, a fixed relationship between asset markets and goods markets is assumed: the adjustment speed of the actual overshooting exchange rate to its long-run level is kept constant over time. In this paper, we introduce a time-varying index for capital market integration via expectation formation in the context of a monetary approach to the exchange rate with sticky prices.
Keywords: 330